FAKTOR-FAKTOR YANG MEMPENGARUHI KECENDERUNGAN KECURANGAN AKUNTANSI DENGAN KEEFEKTIFAN PENGENDALIAN INTERNAL SEBAGAI VARIABEL MODERASI (Studi pada Perusahaan Perkebunan Kelapa Sawit Swasta di Provinsi Riau) - Aswad, Hijratul; Hasan, Amir; Indrawati, Novita (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2017)
The puroposes of this study were obtained empirically about influences ofinformation asymmetry, adherence to the rules of accounting and compliancecompensation to the tendency of accounting fraud with the effectiveness of internalcontrol as a moderating variable. Empirical studies were conducted on private oilpalm plantation companies in Riau Province. The number of samples in this studywere 93 respondents selected based on non-probability sampling method with thedetermination of convenience sampling. In testing the hypothesis using Partial LeastSquare (PLS) analysis. The results of this study indicate that information asymmetryhas a positive effect on the tendency of accounting fraud. adherence to accountingrules and compliance compensation have a negative effect on the tendency ofaccounting fraud. While the effectiveness of internal controls moderates the positiveinfluence of information asymmetry and the negative influence of compensation onthe tendency of accounting fraud. But the effectiveness of internal control did notmoderate the negative influence of compliance to accounting rules on the tendencyto accounting fraud.